Application of CRISPR-Cas9 gene editing technology in basic research, diagnosis and treatment of colon cancer - Meng, Hui; Nan, Manman; Li, Yizhen; Ding, Yi; Yin, Yuhui; Zhang, Mingzhi (Frontiers in Endocrinology, 2023)
Colon cancer is the fourth leading cause of cancer death worldwide, and its progression is accompanied by a complex set of inherited genetic variants. CRISPR/Cas9 can identify new drug resistance or sensitivity mutations in colon cancer, and can use gene editing technology to develop new therapeutic targets, providing personalized treatments that can significantly improve the treatment of colon cancer patients. CRISPR/Cas9 systems are driving advances in biotechnology. RNA-directed Cas enzymes have accelerated the pace of basic research and led to clinical breakthroughs. In recent years, the CRISPR/Cas9 system has been increasingly used in cancer research and treatment, and has achieved remarkable results. This article reviews the rapid development of CRISPR/Cas in colon cancer, from gene editing to transcription regulation, gene knockout, genome-wide CRISPR tools, therapeutic targets, stem cell genomics, immunotherapy, metabolism-related genes and inflammatory bowel disease. In addition, the limitations and future development of CRISPR/Cas9 in colon cancer research were reviewed. In summary, this article reviews the application of CRISPR-Cas9 gene editing technology in the basic research, diagnosis and treatment of colon cancer.